PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PRODUSEN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2021 - Sukmanto, Indria; Fitrianty, Rifda; Rahayu, Sri (Jurnal Manajemen, 2023)
The purpose of this study is to determine the factors that influence the value of coal producing companies listed on the Indonesia Stock Exchange by using Profitability ratios proxied by Return on Equity and Dividend Policy proxied by the Dividend Payout Ratio. The population in this study are 19 coal producing companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2021 period. The number of samples is 6 companies from 19 companies that meet the sampling criteria. The sampling technique used is Purposive sampling. The data analysis technique used is descriptive analysis and panel data regression analysis SPSS version 26. The results of this study indicate that partially profitability has an effect on firm value and dividend policy has no effect on firm value, while simultaneously profitability and dividend policy have an effect on firm value